2019
DOI: 10.1145/3338696
|View full text |Cite
|
Sign up to set email alerts
|

A Luminance-aware Model of Judder Perception

Abstract: The perceived discrepancy between continuous motion as seen in nature and frame-by-frame exhibition on a display, sometimes termed judder, is an integral part of video presentation. Over time, content creators have developed a set of rules and guidelines for maintaining a desirable cinematic look under the restrictions placed by display technology without incurring prohibitive judder. With the advent of novel displays capable of high brightness, contrast, and frame rates, these guidelines are no longer suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In another study, Kuroki et al [2007] measured motion quality up to refresh rate of 480 Hz and found that the quality improves rapidly with increasing refresh rate but saturates after 240 Hz for natural images. Similar trends were also reported by [Chapiro et al 2019;Denes et al 2020;Wilcox et al 2015]. Similar to temporal aliasing, the visibility of flicker decreases with increasing refresh rate.…”
Section: Factors Affecting Perception Of Motion Artifactssupporting
confidence: 87%
See 1 more Smart Citation
“…In another study, Kuroki et al [2007] measured motion quality up to refresh rate of 480 Hz and found that the quality improves rapidly with increasing refresh rate but saturates after 240 Hz for natural images. Similar trends were also reported by [Chapiro et al 2019;Denes et al 2020;Wilcox et al 2015]. Similar to temporal aliasing, the visibility of flicker decreases with increasing refresh rate.…”
Section: Factors Affecting Perception Of Motion Artifactssupporting
confidence: 87%
“…Primarily, there are two main approaches of modeling quality: blackbox metrics and white-box metrics. Black-box metrics [Chapiro et al 2019;Debattista et al 2018] explain the data by fitting an arbitrary function, and typically perform well within the domain of the dataset, but are unable to extrapolate beyond it. White-box metrics on the other hand rely on psychophysical models and are better at extrapolating the predictions.…”
Section: Models Of Motion Qualitymentioning
confidence: 99%
“…Perceived motion quality of panning (horizontal movement on the screen) was investigated recently by Chapiro et al [2019]. The authors measured subjective motion artifact scores for refresh rates typical of modern televisions (30, 60, and 120 Hz) across a range of luminance (2.5-40 cd/m 2 ) and camera panning speeds (2-6.6 deg /s).…”
Section: Motion Quality In Filmsmentioning
confidence: 99%
“…We follow their approach in our target application and also optimize rendering quality under a constrained budget using a model. However, our model accounts for the velocity of motion, which was shown to be a major factor affecting motion quality [Chapiro et al 2019]. Furthermore, our intention is to build an explainable model, accounting for the underlying mechanisms of the visual system, which can generalize across a wide range of input parameters.…”
Section: Refresh Rate Vs Resolutionmentioning
confidence: 99%
“…An accurate presentation of stimuli is a prerequisite for accurate results of visual perception experiments. However, most modern monitors present motion objects at discrete locations, showing an approximate continuous motion process (Chapiro et al, 2019). Motion blur will occur when the motion speed or motion frequency is too high; it violates the assumption of smooth motion and causes stimulus distortion and false experimental results (Tourancheau et al, 2009;Watson and Ahumada, 2011).…”
Section: Introductionmentioning
confidence: 99%